2014
DOI: 10.1620/tjem.233.205
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Measuring the ATP-Related Compounds in Human Erythrocytes

Abstract: The ATP-related compounds in whole blood or red blood cells have been used to evaluate the energy status of erythrocytes and the degradation level of the phosphorylated compounds under various conditions, such as chronic renal failure, drug monitoring, cancer, exposure to environmental toxics, and organ preservation. The complete interpretation of the energetic homeostasis of erythrocytes is only performed using the compounds involved in the degradation pathway for adenine nucleotides alongside the uric acid v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…More RBCs could be analyzed to increase sensitivity, but results would then be above the limit of quantification for ATP and GTP when assaying more than 10×10 6 cells. However, for all validation runs the adjusted LLOQ was still relatively sensitive at 0.625 pmol/sample; a lower amount than other methods published for the measurement of inosine or its IMP metabolite (17, 34). Additionally, because ITP is not incorporated into RNA or DNA, previous methods have not, to our knowledge, attempted to quantify this nucleotide.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…More RBCs could be analyzed to increase sensitivity, but results would then be above the limit of quantification for ATP and GTP when assaying more than 10×10 6 cells. However, for all validation runs the adjusted LLOQ was still relatively sensitive at 0.625 pmol/sample; a lower amount than other methods published for the measurement of inosine or its IMP metabolite (17, 34). Additionally, because ITP is not incorporated into RNA or DNA, previous methods have not, to our knowledge, attempted to quantify this nucleotide.…”
Section: Discussionmentioning
confidence: 76%
“…As mentioned earlier, DBS has been used for the measurement of many endogenous biomarkers including nucleotides, but stability of this matrix has not been thoroughly evaluated (22, 31, 32). Other studies that have measured nucleotide pools in RBC samples have reported that immediate processing is a necessity for accurate results (17, 33). Both the RBCs and DBS samples reported here were stored at −70°C for 815–929 days prior to this analysis, but DBS appeared to have a breakdown of TP to the MP compared to RBCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Aragon-Martinez et al developed a liquid chromatographic method for quantification of ATP-related compounds in erythrocytes using a diode array detector [18]. In this method, the authors reported sensitivity for ATP-compounds with limits of detection from 0.001 to 0.097 µmol/L and quantification limits from 0.004 to 0.294 µmol/L [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Aragon-Martinez et al developed a liquid chromatographic method for quantification of ATP-related compounds in erythrocytes using a diode array detector [18]. In this method, the authors reported sensitivity for ATP-compounds with limits of detection from 0.001 to 0.097 µmol/L and quantification limits from 0.004 to 0.294 µmol/L [18]. Similarly, McFarland and coworkers developed a combined liquid chromatography UV-Vis assay for detection of adenosine, inosine, and hypoxanthine and detected urate and xanthine via coulometric detection at 150 and 450 mV [19].…”
Section: Discussionmentioning
confidence: 99%